Conductive films and display devices

JP2026165783APending Publication Date: 2026-10-14TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058363
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本開示の一側面によれば、伝送ロスが抑えられ密着性が高い導電性フィルム及びこれを備える表示装置が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165783000001_ABST
    Figure 2026165783000001_ABST
Patent Text Reader

Abstract

To provide a conductive film that minimizes transmission loss and exhibits high adhesion. [Solution] A conductive film comprising a base material and a conductor located on one surface side of the base material, wherein in a cross-sectional image obtained by observing a cross section along the direction of extension of the conductive wires, the surface of the conductive wires opposite to the base material is defined as the first surface, the length of the straight line connecting the ends of the first surface is defined as L1, and the length of the first surface is defined as L2, and the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a conductive film and a display device.

Background Art

[0002] A transparent antenna mounted with a conductive substrate (conductive film) having transparency and conductivity may be mounted on the surface of a touch panel or a display. In recent years, along with the enlargement and diversification of touch panels and displays, conductive films are required to have high transparency, high conductivity, and flexibility.

[0003] For example, Patent Document 1 discloses a transparent conductive film that includes a transparent film having grooves on the surface and conductive parts present in the grooves, wherein the conductive parts are composed of a siloxane layer containing palladium and a conductive material, and the ratio of the line width of the conductive layer to the height relative to the line width falls within a specific range.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] Meanwhile, conductive films are required to have low transmission loss. In addition, the conductive film is required to have high adhesion to pads and the like provided on the conductor-side surface.

[0006] One aspect of the present disclosure provides a conductive film with suppressed transmission loss and high adhesion, and a display device including the same.

Means for Solving the Problems

[0007] One aspect of this disclosure provides a conductive film comprising a substrate and a conductor located on one surface side of the substrate, wherein in a cross-sectional image obtained by observing a cross section along the direction of extension of the conductive wires, the surface of the conductive wires opposite to the substrate is defined as the first surface, the length of the straight line connecting the ends of the first surface is L1, and the length of the first surface is L2, and the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.5.

[0008] Another aspect of this disclosure is to provide a display device comprising the conductive film described above. [Effects of the Invention]

[0009] According to one aspect of this disclosure, a conductive film with reduced transmission loss and high adhesion, and a display device equipped therewith are provided. [Brief explanation of the drawing]

[0010] [Figure 1] Figure 1 is a schematic plan view showing a conductive film according to one embodiment. [Figure 2] Figure 2 is a cross-sectional view taken along the line II-II in Figure 1. [Figure 3] Figure 3 is an enlarged plan view of the conductor side of a conductive film according to one embodiment. [Figure 4] Figure 4 is a schematic diagram of a cross-sectional image obtained by observing the cross-section along the line IVa-IVa in Figure 3. [Figure 5] Figure 5 is a schematic cross-sectional view showing the manufacturing method of the conductive film shown in Figure 1. [Figure 6] Figure 6 is a schematic cross-sectional view showing the manufacturing method of the conductive film shown in Figure 1. [Figure 7] Figure 7 is a cross-sectional view showing one embodiment of the container. [Modes for carrying out the invention]

[0011] This disclosure is not limited to the following examples.

[0012] <Conductive film> A conductive film according to one embodiment of the present disclosure will be described below. Figure 1 is a schematic plan view showing a conductive film according to the present embodiment. Figure 2 is a cross-sectional view taken along the line II-II in Figure 1. In other words, Figure 2 is a cross-section of the conductive film 100 in the thickness direction. The conductive film 100 shown in Figures 1 and 2 comprises a substrate 10, a resin layer 20 disposed on the substrate 10 and having a trench 25 opening to the surface opposite to the substrate 10, and a conductor 50 provided in the trench 25. The resin layer 20 has a first layer 30 and a second layer 40 from the substrate 10 side. The substrate 10 and the resin layer 20 are in direct contact. The trench 25 penetrates the resin layer 20 in the thickness direction. The conductive film 100 can be made thinner compared to the case where another resin layer is provided between the substrate 10 and the resin layer 20. Therefore, the resulting display device can be made smaller.

[0013] (base material) The substrate 10 is in the form of a film. The substrate 10 may be transparent. The substrate 10 may have light transmittance to the extent required when the conductive film 100 is incorporated into a display device, for example. Specifically, the total light transmittance of the substrate may be 90 to 100%. The haze of the substrate may be 0 to 5%.

[0014] The base material 10 includes a resin portion. Examples of materials for the resin portion include polyethylene terephthalate (PET), polycarbonate (PC), polyethylene naphthalate (PEN), cycloolefin polymer (COP), polymethyl methacrylate (PMMA), or polyimide (PI).

[0015] The base material 10 may contain a filler. The filler may be in the form of particles. The filler may be an inorganic filler or an organic filler. The filler may also be an insulating material. Examples of fillers include silica filler particles and zirconia filler particles.

[0016] At the interface between the base material 10 and the resin layer 20, the filler may protrude toward the resin layer 20. The expression "the filler protrudes toward the resin layer 20" means that a part of the filler is present inside the resin layer 20 and a part thereof is present inside the base material 10. At the interface between the base material 10 and the conductor 50, the filler may protrude toward the conductor 50. The expression "the filler protrudes toward the conductor 50" means that a part of the filler is present inside the conductor 50 and a part thereof is present inside the base material 10.

[0017] The thickness of the base material 10 may be 10 μm or more, 20 μm or more, or 35 μm or more, and may be 500 μm or less, 200 μm or less, or 100 μm or less.

[0018] (Resin Layer) The first layer 30 is a resin layer including a first resin portion and a plurality of inorganic particles.

[0019] The first resin portion may be transparent. The first resin portion may be a cured product of a photocurable resin or a thermosetting resin. Examples of the photocurable resin or thermosetting resin include acrylic resin, amino resin, cyanate resin, isocyanate resin, polyimide resin, epoxy resin, oxetane resin, polyester, allyl resin, phenol resin, benzoxazine resin, xylene resin, ketone resin, furan resin, COPNA resin, silicon resin, dicyclopentadiene resin, benzocyclobutene resin, episulfide resin, ene-thiol resin, polyazomethine resin, polyvinyl benzyl ether compound, acenaphthylene, and ultraviolet curable resins containing functional groups that cause a polymerization reaction under ultraviolet light, such as unsaturated double bonds, cyclic ethers, and vinyl ethers. These photocurable resins or thermosetting resins may be used singly or in combination of two or more types.

[0020] The inorganic particles may be one or more types of inorganic particles selected from Pd, Cu, Ni, Co, Au, Ag, Rh, Pt, In, and Sn, and may contain Pd. The inorganic particles may be used singly or in combination of two or more types of inorganic particles.

[0021] The shape of the inorganic particles is not particularly limited and may be spherical, ellipsoidal, polyhedral, plate-like, flaky, columnar, etc.

[0022] The average particle size of the inorganic particles may be 10 nm or less, 8 nm or less, or 5 nm or less, from the viewpoint of the conductive film 100 having excellent transparency. The average particle size of the inorganic particles may also be, for example, 0.1 nm or more, 0.5 nm or more, or 1 nm or more. The average particle size of the inorganic particles is calculated by observing a cross-section of the conductive film 100 in the thickness direction using a scanning electron microscope (SEM), measuring the maximum length of each inorganic particle present in the observation area, and averaging the results.

[0023] The thickness of the first layer 30, or the thickness of the first resin part, may be, for example, 10 nm or more, 15 nm or more, or 20 nm or more, and may also be 300 nm or less, 250 nm or less, or 200 nm or less.

[0024] The second layer 40 is a resin layer mainly composed of the second resin portion. The second layer 40 may or may not contain inorganic particles. The second resin portion may be transparent. The second resin portion may be made of a different material from the first resin portion, or it may be made of the same material. The second resin portion may be a cured product of a photocurable resin or a thermosetting resin. Examples of photocurable resins or thermosetting resins include acrylic resins, urethane resins, amino resins, cyanate resins, isocyanate resins, polyimide resins, epoxy resins, oxetane resins, polyesters, allyl resins, phenolic resins, benzoxazine resins, xylene resins, ketone resins, furan resins, COPNA resins, silicon resins, dicyclopentadiene resins, benzocyclobutene resins, episulfide resins, ene-thiol resins, polyazomethine resins, polyvinyl benzyl ether compounds, acenaphthylene, and UV-curable resins containing functional groups that undergo polymerization reactions under ultraviolet light, such as unsaturated double bonds, cyclic ethers, and vinyl ethers. These photocurable resins or thermosetting resins may be used individually or in combination of two or more types.

[0025] The thickness of the second layer 40, or the thickness of the second resin part, may be, for example, 1 μm or more, 1.5 μm or more, or 2 μm or more, and may also be 5 μm or less, 4 μm or less, or 3 μm or less.

[0026] The thickness of the resin layer 20 may be, for example, 1 μm or more, 1.5 μm or more, or 2 μm or more, and may also be 5 μm or less, 4 μm or less, or 3 μm or less.

[0027] The trench 25 opens to the surface opposite to the substrate 10 and extends onto the resin layer 20. The trench 25 includes portions that form a pattern corresponding to the pattern of the conductor 50. As shown in Figure 2, the width of the trench 25 may narrow from the side of the resin layer 20 away from the substrate 10 towards the substrate 10, or the width of the trench 25 may be substantially constant in the depth direction.

[0028] The width and depth of the trench 25 may generally be substantially the same as the width and height of the conductor 50, respectively. That is, the height of the surface of the resin layer 20 from the surface 10a of the substrate 10 may be the same as the height of the surface of the conductor 50 from the surface 10a of the substrate 10. The height of the surface of the resin layer 20 from the surface 10a of the substrate 10 may be lower or higher than the height of the surface of the conductor 50 from the surface 10a of the substrate 10. In this specification, the width of the trench 25 means the maximum width in the direction perpendicular to the extension direction of the trench, and the depth of the trench 25 means the maximum depth in the thickness direction of the resin layer. The ratio of the depth of the trench 25 to the width of the trench 25 may be the same as the aspect ratio of the conductor 50, which will be described later.

[0029] (conductor) Figure 3 is an enlarged plan view of the conductive film 100 on the side facing the conductor 50. The conductor 50 is layered. The conductor 50 has a pattern in which multiple conductive wires are arranged in a mesh-like manner. A conductor 50 having a mesh-like pattern can function well as, for example, a radiating element of an antenna. The trench 25 and the conductor 50 are provided over a portion of the surface 10a of the substrate 10. The mesh-like pattern of the conductor 50 may be a regular pattern or an irregular pattern.

[0030] In Figure 3, the conductor 50 includes conductive wires 51 and 52. In Figure 3, conductive wires 51 and 52 are marked with a dot pattern. Conductive wires 51 and 52 extend linearly in the direction of extension on the substrate 10. Conductive wires 51 and 52 extend along two respective directions. In Figure 3, the rectangular areas other than conductive wires 51 and 52 are the parts where the second layer 40 is exposed. Hereinafter, the direction of extension of conductive wire 51 will be described as direction D1, the width direction of conductive wire 51 as direction D2, and the height direction of conductive wire as direction D3. Directions D1 to D3 are orthogonal to each other. The direction of extension of conductive wire 51 is the direction in which the center line of the straight line approximating one side edge in direction D2 of conductive wire 51 and the straight line approximating the other side edge extends.

[0031] Figure 4 is a schematic diagram of a cross-sectional image P1 obtained by observing the cross-section along the IVa-IVa line in Figure 3 using a scanning electron microscope (SEM). The cross-section along the IVa-IVa line in Figure 3 is a cross-section along the direction D1 of the conductive wire 51. The cross-sectional image P1 may be a binarized version of the captured image. "Cross-section along direction D1" means that the cross-section is not only perfectly parallel to direction D1, but also approximately parallel. Figure 4 is a schematic diagram of a cross-sectional image obtained by observing the cross-section along the IVa-IVa line in Figure 3. The angle between the IVa-IVa line and direction D1 may be 0 to 4°. The angle between the IVa-IVa line and direction D1 may also be 0.5 to 4° from the viewpoint of reflecting the surface state of the conductive wire 51 in direction D2. In other words, the cross-section to be observed for the conductive wire 51 may be a surface inclined at 0.5 to 4° with respect to direction D1.

[0032] Furthermore, if the conductor 50 constitutes a pattern in which multiple conductive wires are arranged in a mesh, the surface state of the conductive wire 51 in directions D1 and D2 can be adequately reflected by observing the cross section of the conductive wire 51 to be observed in direction D1 as half the pitch of the mesh pattern, and in direction D2 as the width of the conductive wire. If the inclination angle of the cross section of the conductive wire 51 to be observed is D with respect to direction D1, the mesh pitch is P, and the width of the conductive wire is w, the above range can be observed by setting the inclination angle D to satisfy the following equation (1). D = 22.737 × (P / 2) -0.993 ×w···(1)

[0033] In the cross-sectional image P1, the surface of the conductive wire 51 opposite to the base material 10 is defined as the first surface 51a. The length of the straight line S1 connecting ends b1 and b2 of the first surface 51a in the cross-sectional image P1 is defined as L1. The length of the first surface 51a is defined as L2. In this case, the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.5. When the ratio (L2 / L1) is greater than 1.0, the adhesion between the conductive film and the pad portion formed on its surface is improved. Also, when the ratio (L2 / L1) is 1.5 or less, transmission loss is suppressed.

[0034] The ratio (L2 / L1) may be 1.1 or higher, or 1.2 or higher, as this further improves adhesion. The ratio (L2 / L1) may be 1.4 or lower, or 1.3 or lower, as this further reduces transmission loss. The ratio (L2 / L1) can be changed by adjusting the plating time of the conductive wire, the current value of the electroplating, the content of the brightener component in the plating solution, etc.

[0035] In the cross-sectional image P1, point 51a1 is the highest point (the apex of the convex portion H1) of the conductive wire 51 on the first surface 51a in direction D3. The imaginary line S2 is a straight line along direction D3 that includes point 51a1. Point 51a2 is the lowest point (the bottom of the concave portion H2) of the conductive wire 51 on the first surface 51a in direction D3. The imaginary line S3 is a straight line along direction D3 that includes point 51a2. The imaginary line S4 is a straight line located midway between imaginary lines S2 and S3. Points 51a3 to 51a6 are the intersections of imaginary line S4 and the first surface 51a. Region r1 is the region from point 51a1 to the center (the region enclosed by imaginary lines S2 and S4). Region r2 is the region from point 51a2 to the center (the region enclosed by imaginary lines S3 and S4).

[0036] The total length of the first surface 51a included in region r1 may be shorter than the total length of the first surface 51a included in region r2. In this case, low resistance can be achieved while ensuring adhesion of the conductive film. In Figure 3, the total length of the first surface 51a included in region r1 is the sum of the length of the first surface 51a between points 51a3 and 51a4, and the length of the first surface 51a between points 51a5 and 51a6. In Figure 3, the total length of the first surface 51a included in region r2 is the sum of the length of the first surface 51a between end b1 and point 51a3, the length of the first surface 51a between points 51a4 and 51a5, and the length of the first surface 51a between point 51a6 and end b2.

[0037] In Figure 3, the cross-sectional image obtained by observing the cross-section of the IVb-IVb line also shows that the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.5. The cross-section of the IVb-IVb line in Figure 3 is a cross-section along the direction D1 of the conductive wire 51. When the cross-section of the IVa-IVa line in Figure 3 is considered the first cross-section and the cross-section of the IVb-IVb line is considered the second cross-section, the second cross-section is closer to the edge 51e of the conductive wire 51 in the direction D2 than the first cross-section in the direction D2. The ratio (L2 / L1) in the cross-sectional image of the second cross-section may be smaller than the ratio (L2 / L1) in the cross-sectional image P1 of the first cross-section. The current flowing through the conductive wire 51 is concentrated at the edge 51e of the conductive wire 51. Therefore, transmission loss can be suppressed by reducing the ratio (L2 / L1) near the edge 51e of the conductive wire 51. Furthermore, in the central part of the conductive wire 51, including the center line CL in direction D2, increasing the ratio (L2 / L1) does not easily lead to transmission loss. Therefore, by making the ratio (L2 / L1) in the cross-sectional image of the second cross-section smaller than the ratio (L2 / L1) in the cross-sectional image P1 of the first cross-section, the adhesion can be further improved while effectively suppressing transmission loss.

[0038] The arithmetic mean roughness Ra of the conductive wire 51 in the cross-sectional image P1 may be 60 nm or more, or 65 nm or more, in order to further improve adhesion. The arithmetic mean roughness of the conductive wire 51 in the cross-sectional image P1 may be 130 nm or less, or 125 nm or less, in order to further suppress transmission loss.

[0039] The maximum height Rz of the conductive wire 51 in the cross-sectional image P1 may be 450 nm or more, or 470 nm or more, in order to further improve adhesion. The maximum height Rz of the conductive wire 51 in the cross-sectional image P1 may be 700 nm or less, or 680 nm or less, in order to further suppress transmission loss.

[0040] The width w of the conductive wires 51 and 52 may be 1.5 μm or less, or 1.3 μm or less. By setting it within this range, the effect of high transmittance can be obtained. Alternatively, the width w of the conductive wires 51 and 52 may be 0.5 μm or more, or 0.8 μm or more. By setting it within this range, the effect of low resistance can be obtained.

[0041] The aspect ratio of the conductive wires 51 and 52, which is the ratio of the width w to the height h, may be greater than 1, 2 or greater, or 3 or greater. This allows for the effect of reducing resistance while suppressing the visibility of the conductor 50. The height h of the conductive wires 51 and 52 should be set within the range that satisfies the aforementioned width w and aspect ratio.

[0042] The conductive wires 51 and 52 may be composed of a single metal or of multiple metals of different types. The conductive wires 51 and 52 may be formed by metal plating. The metal plating may include at least one metal selected from, for example, copper, nickel, cobalt, palladium, silver, gold, platinum, and tin, and may also include copper. The conductor 50 may further contain nonmetallic elements such as phosphorus, to the extent that conductivity is maintained.

[0043] When the conductive wires 51 and 52 have a seed layer and an upper metal plating layer, the metal constituting the seed layer and the metal constituting the upper metal plating layer may be the same or different. For example, the seed layer may contain nickel and the upper metal plating layer may contain copper. The upper metal plating layer may consist of a copper plating layer formed on the seed layer and an uppermost layer formed on the copper plating layer that contains gold or palladium.

[0044] Although a conductive film according to one embodiment has been described above, the conductive film of this disclosure is not limited to the above embodiment. For example, the conductive film 100 has a first layer 30 and a second layer 40 as the resin layer 20, but the resin layer may be a single layer. Also, in the conductive film of this disclosure, when the resin layer 20 is the first resin layer, the second resin layer may be provided on the surface of the substrate opposite to the first resin layer.

[0045] (Second resin layer) The second resin layer may be transparent. The hard coat layer may be a cured product of a photocurable resin or a thermosetting resin. Examples of photocurable or thermosetting resins include acrylic resins, amino resins, cyanate resins, isocyanate resins, polyimide resins, epoxy resins, oxetane resins, polyesters, allyl resins, phenolic resins, benzoxazine resins, xylene resins, ketone resins, furan resins, COPNA resins, silicon resins, dicyclopentadiene resins, benzocyclobutene resins, episulfide resins, enethiol resins, polyazomethine resins, polyvinylbenzyl ether compounds, acenaphthylene, and UV-curable resins containing functional groups that undergo polymerization reactions under ultraviolet light, such as unsaturated double bonds, cyclic ethers, and vinyl ethers. These photocurable or thermosetting resins may be used individually or in combination of two or more types.

[0046] The second resin layer may contain a filler. The filler may be in the form of particles. The filler may be an inorganic filler or an organic filler. The filler may also be an insulating material. Examples of fillers include silica filler particles and zirconia filler particles.

[0047] The thickness of the second resin layer may be, for example, 5 nm or more, 10 nm or more, 20 nm or more, 30 nm or more, 40 nm or more, or 50 nm or more, and may also be 10 μm or less, 5 μm or less, 2 μm or less, 1 μm or less, 800 nm or less, 600 nm or less, 500 nm or less, or 400 nm or less.

[0048] <Method for manufacturing conductive film> The following describes a method for manufacturing a conductive film according to one embodiment of the present disclosure. Figures 5 and 6 are schematic cross-sectional views showing an example of a method for manufacturing the conductive film 100 shown in Figure 1. In the method according to this embodiment, first, as shown in Figure 5(a), a first layer 30 is formed on one surface 10a of the film-like substrate 10.

[0049] The first layer 30 is formed, for example, by a method that includes applying a coating liquid containing a resin component forming the first resin part, inorganic particles, and a solvent onto the substrate 10, and removing the solvent from the coating film on the substrate 10. The step in Figure 5(a) may be a step of preparing a laminate comprising the substrate 10 and the first layer 30.

[0050] As shown in Figure 5(b), a coating film 40' of a resin composition containing a resin component that forms the second resin portion is formed on the surface 30a of the first layer 30. The step in Figure 5(b) may also be a step of preparing a laminate comprising the substrate 10, the first layer 30, and the coating film 40' in this order.

[0051] As shown in Figure 5(c) and Figure 6(a), a second layer 40 having trenches 45 is formed by an imprint method using a mold 55 having protrusions 55a. In this step, the mold 55 having protrusions 55a of a predetermined shape is moved in the direction indicated by arrow A to press it into the coating film 40' (Figure 5(c)). The mold 55 may be pressed in until the tip of the protrusions 55a reaches the first layer 30. In this state, the second resin part is cured as necessary. If the second resin part before curing contains a photocurable resin, the second resin part is cured by irradiating it with light such as ultraviolet light. After that, the mold 55 is removed to form trenches 45 having a shape that is the inverse of the shape of the protrusions 55a of the mold 55 (Figure 6(a)). The method for forming the trenches 45 is not limited to the imprint method, and for example, the trenches 45 may be formed by laser, dry etching, or photolithography. The steps in Figure 5(c) and Figure 6(a) may be steps to form a second layer 40 having a trench 45 in a laminate comprising a base material 10, a first layer 30, and a second layer 40 in that order.

[0052] The mold 55 may be made of quartz, Ni, UV-curable liquid silicone rubber (PDMS), etc. The shape of the protrusion 55a of the mold 55 is designed according to the shape of the trench 25 to be formed.

[0053] As shown in Figure 6(b), the first resin portion exposed from the bottom surface of the trench 45 is removed. This forms a trench (groove) 35 in the first layer 30. This forms a trench 25 consisting of trench 35 and trench 45. By removing the first resin portion, inorganic particles are exposed on the bottom surface of the trench 25. The first resin portion may be removed by etching, such as dry etching, after removing the mold 55. The step in Figure 6(b) may also be a step of forming a trench 35 that opens on the surface of the first layer 30 opposite to the substrate 10 in a laminate comprising a base material 10, a first layer 30, and a second layer 40 in this order.

[0054] As shown in Figure 6(c), a conductor 50 is formed to fill the trench 25. The conductor 50 may be formed by an electroless plating method in which metal plating is grown from the substrate 10. By immersing the laminate on which the trench 25 is formed in an electroless plating solution containing metal ions, the metal plating can be grown from the bottom of the trench 25 to form the conductor 50. By forming the conductor 50 to fill the trench 25, a conductive film 100 can be obtained.

[0055] The electroless plating solution contains ions of the metals that make up the conductor 50. The electroless plating solution may further contain phosphorus, boron, iron, etc.

[0056] The temperature of the electroless plating solution when immersing the laminate in it may be, for example, 40 to 90°C. The immersion time in the electroless plating solution varies depending on the thickness of the conductor 50, but may be, for example, 10 to 30 minutes.

[0057] A conductive wire having a seed layer and an upper metal plating layer can be formed by a method that includes forming a seed layer (first metal layer) on a substrate 10 and forming an upper metal plating layer (second metal layer) on the seed layer. A laminate with trenches 25 formed on it is immersed in an electroless plating solution for forming the seed layer to form a metal plating as a seed layer on the substrate 10. Subsequently, the laminate having the seed layer can be immersed in an electroless plating solution for forming the upper metal plating layer to form the upper metal plating layer on the seed layer. Before forming the upper metal plating layer, a catalyst may be adsorbed onto the seed layer, and the upper metal plating layer may be formed starting from the catalyst adsorbed on the seed layer. The upper metal plating layer may also be formed by electroplating.

[0058] The thickness of the seed layer may be 10 nm or more, 30 nm or more, or 50 nm or more, and may be 500 nm or less, 300 nm or less, or 100 nm or less.

[0059] <Display device> The following describes a display device according to one embodiment of the present disclosure. Figure 7 is a cross-sectional view of the display device according to the present embodiment. The display device 500 shown in Figure 7 comprises an image display unit 60 having an image display area 60S, a conductive film 100, a polarizing plate 70, and a cover glass 80. The conductive film 100, the polarizing plate 70, and the cover glass 80 are laminated in this order from the image display unit 60 side on the image display area 60S side of the image display unit 60. The conductive film 100 is incorporated as a planar transparent antenna.

[0060] The display device may be, for example, a liquid crystal display device or an organic EL display device.

[0061] The configuration of the display device is not limited to the form shown in Figure 7 and can be modified as needed. For example, a polarizing plate 70 may be provided between the image display unit 60 and the conductive film 100. The image display unit 60 may be, for example, a liquid crystal display unit. The polarizing plate 70 and cover glass 80 can be those commonly used in display devices. The polarizing plate 70 and cover glass 80 are not necessarily required.

[0062] While display devices were given as an example of devices to which conductive films can be applied, conductive films may also be applied to devices other than display devices. For example, conductive films may be applied to glass in buildings or automobiles as transparent antennas. [Examples]

[0063] This disclosure is not limited to the following embodiments.

[0064] <Manufacturing of conductive films> (Example 1) A conductive film was manufactured by further adding a second resin layer on the surface opposite to the resin layer of the substrate, as shown in Figures 1-4. Specifically, first, polyethylene terephthalate (PET) film (thickness: 100 μm, manufactured by Toyobo Co., Ltd., product name "A4360") was prepared as the substrate.

[0065] A coating solution for forming the first layer was prepared, containing Pd microparticles (average particle size: 5 nm), acrylic resin, and a solvent. The coating solution was applied onto a PET film using a bar coater to form a coating film. The solvent was removed from the coating film using a hot air drying oven. Next, the coating film was cured by irradiating it with ultraviolet light using a UV treatment device. This formed a first layer (thickness: 5 nm) containing Pd microparticles (inorganic particles).

[0066] A coating solution containing acrylic resin and a solvent was prepared for forming a second resin layer. The coating solution was applied to the side of the PET film opposite to the first layer using a bar coater to form a coating film. The solvent was removed from the coating film using a hot air drying oven. Next, the coating film was cured by irradiating it with ultraviolet light using a UV treatment device. This formed a second resin layer (thickness: 300 nm).

[0067] A coating solution containing acrylic resin and a solvent was prepared for forming a second layer. The coating solution was applied to the surface of the first layer opposite to the PET film to form a coating film. A Ni mold with a protrusion 1 μm wide and 2 μm high was prepared. The mold was pressed into the coating film so that the tip of the protrusion reached the surface of the first layer, and the coating film was irradiated with ultraviolet light to cure it. By removing the mold from the cured coating film, a second layer (thickness: 2 μm) was formed, in which linear trenches (width: 1 μm, height: 2 μm) with a mesh-like pattern were formed, intersecting each other and opening on the surface opposite to the first layer, and a laminate was obtained. The first and second layers constitute the first resin layer.

[0068] The laminate was placed inside a vacuum chamber, and an ashing treatment was performed on the surface of the second layer of the laminate to remove the resin portion of the first layer so that the PET film was exposed through the trenches in the resin layer.

[0069] The laminate, after ashing, was immersed in an electroless plating solution to grow Cu plating, forming a conductor containing multiple conductive wires made of Cu within the trenches. The conductor is a coplanar line with a mesh-like pattern. This resulted in a conductive film comprising a second resin layer, a substrate, the first layer, and the second layer in that order. The aspect ratio, obtained by dividing the height dimension of the conductive wires by the width dimension, was 2. The arithmetic mean roughness of the surface of the second resin layer, measured by AFM (atomic force microscope), was 30 nm.

[0070] (Examples 2 and 3, Comparative Examples 1 and 2) A conductive film was obtained in the same manner as in Example 1, except that the content of the brightener component in the electroless plating solution was changed.

[0071] <Cross-sectional observation> (Example 1) The conductive film was observed in cross-sections along the direction of the conductive wire's extension and its height. The measurement surface was formed by applying an Ar beam from the substrate side using a cross-section polisher (JEOL, model name "M-09010", grinding conditions: acceleration voltage 4kV, processing time 7 hours). The angle between the direction of the conductive wire's extension and the measurement surface was set to 1°.

[0072] The measurement surface was observed using a SEM (Hitachi High-Technologies Corporation, device name "SU8000", measurement conditions: acceleration voltage 5kV, magnification 10,000x), and cross-sectional images were captured. A portion of the cross-sectional image (size: 1280 x 900 pixels) was cropped. The cropped image was binarized by performing the following operation. From the binarized cross-sectional image, the length L1 of the straight line connecting the edges of the first surface, the length of the first surface L2, the arithmetic mean roughness Ra, and the maximum height Rz were measured. The ratio (L2 / L1) was also calculated. Measurements were performed on five cross-sections, A to E, along the extension direction and height direction of the conductive wire. Cross-sections A to E are arranged sequentially along the width direction of the conductive wire. Cross-sections A and E are located near the edge in the width direction of the conductive wire, and cross-section C is located in the center of the conductive wire. The results are shown in Table 1. The average value of the ratio (L2 / L1) is shown in Table 2. The average value of Ra was 90 nm. The average value of Rz was 566 nm.

[0073] It can be confirmed that the ratio of section A (L2 / L1) is smaller than the ratio of sections B and C (L2 / L1). It can be confirmed that the ratio of section B (L2 / L1) is smaller than the ratio of section C (L2 / L1). It can be confirmed that the ratio of section D (L2 / L1) is smaller than the ratio of section C (L2 / L1). It can be confirmed that the ratio of section E (L2 / L1) is smaller than the ratio of sections C and D (L2 / L1).

[0074] In the cross-sectional image, it was confirmed that the total length of the first surface included in the region from the highest point in the height direction of the conductive wires of the first surface to the center is shorter than the total length of the first surface included in the region from the lowest point in the height direction of the conductive wires of the first surface to the center.

[0075] (Examples 2 and 3, Comparative Examples 1 and 2) L1, L2, Ra, and Rz were measured in the same manner as in Example 1. The average values ​​of the ratio (L2 / L1) are shown in Table 2.

[0076] In the cross-sectional images of Examples 2 and 3, it was confirmed that the total length of the first surface included in the region from the highest point in the height direction of the conductive wires on the first surface to the center was shorter than the total length of the first surface included in the region from the lowest point in the height direction of the conductive wires on the first surface to the center.

[0077] In the cross-sectional images of Examples 2 and 3, when observing the first cross-section and the second cross-section, which is closer to the edge of the conductive wire than the first cross-section in a direction perpendicular to the direction of extension of the conductive wire, it was confirmed that the ratio (L2 / L1) in the cross-sectional image of the second cross-section was smaller than the ratio (L2 / L1) in the cross-sectional image of the first cross-section.

[0078] <Evaluation of adhesion> (Examples 1-3, Comparative Examples 1 and 2) Pad areas were formed on the mesh-like conductive surface of each conductive film using silver paste. Tape was applied to the formed pad areas, and the tape was removed to check for delamination between the pad area and the conductor. Cases where no delamination occurred were rated "A," and cases where delamination occurred were rated "B." The results are shown in Table 2.

[0079] <Evaluation of transmission loss> (Examples 1-3, Comparative Examples 1 and 2) For each example, the transmission loss was measured using a microwave network analyzer (Keysight, model name "N5247A PNA-X") by contacting probes with both ends of the conductor of the conductive film. A loss of 1.5 dB or less was rated "A," and a loss greater than 1.5 dB was rated "B." The results are shown in Table 2.

[0080] [Table 1]

[0081] [Table 2]

[0082] One aspect of this disclosure relates to the following [1] to [7]. [1] Substrate and A conductor comprising multiple linearly extending conductive wires, located on one surface side of the substrate, Equipped with, A conductive film in which, in a cross-sectional image obtained by observing a cross-section along the direction of extension of a conductive wire, the surface opposite to the substrate of the conductive wire is defined as the first surface, the length of the straight line connecting the ends of the first surface is L1, and the length of the first surface is L2, the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.5. [2] In a cross-sectional image, the total length of the first surface included in the region from the highest point in the height direction of the conductive wires of the first surface to the center is shorter than the total length of the first surface included in the region from the lowest point in the height direction of the conductive wires of the first surface to the center. The conductive film according to [1]. [3] A conductive film according to [1] or [2], wherein, when a first cross section and a second cross section that is closer to the edge of the conductive wire than the first cross section in a direction perpendicular to the direction of extension and height of the conductive wire are observed as cross sections along the direction of extension of the conductive wire, the ratio (L2 / L1) in the cross-sectional image of the second cross section is smaller than the ratio (L2 / L1) in the cross-sectional image of the first cross section. [4] Further comprising a resin layer located on the other surface side of the substrate, The resin layer includes a resin part and a filler. A conductive film according to any one of [1] to [3], wherein the arithmetic mean roughness of the first surface in the cross-sectional image is greater than the arithmetic mean roughness of the surface of the resin layer. [5] A conductive film as described in any of [1] to [4], wherein the aspect ratio obtained by dividing the height dimension of the conductive wire by the width dimension is greater than 1. [6] A conductive film according to any one of [1] to [5], wherein the conductor constitutes a pattern in which conductive wires are arranged in a mesh. A display device comprising a conductive film as described in any of [7] [1] to [6]. [Explanation of Symbols]

[0083] 10...Substrate, 20...Resin layer, 50...Conductor, 51, 52...Conductive wire, 51a...First surface, 51e...Edge of conductive wire, 100...Conductive film, 500...Display device, P1...Cross-sectional image, r1, r2...Region.

Claims

1. Substrate and A conductor comprising multiple linearly extending conductive wires, located on one surface side of the substrate, Equipped with, A conductive film in which, in a cross-sectional image obtained by observing a cross-section along the extending direction of the conductive wire, the surface of the conductive wire opposite to the substrate is defined as the first surface, the length of the straight line connecting the ends of the first surface is L1, and the length of the first surface is L2, the ratio of L2 to L1 (L2 / L1) is greater than 1.0 and less than or equal to 1.

5.

2. The conductive film according to claim 1, wherein in the cross-sectional image, the total length of the first surface included in the region from the highest point in the height direction of the conductive wires on the first surface to the center is shorter than the total length of the first surface included in the region from the lowest point in the height direction of the conductive wires on the first surface to the center.

3. The conductive film according to claim 1, wherein when a first cross-section and a second cross-section, which is closer to the edge of the conductive wire than the first cross-section in a direction perpendicular to the extending direction and height direction of the conductive wire are observed as cross-sections along the extending direction of the conductive wire, the ratio (L2 / L1) in the cross-sectional image of the second cross-section is smaller than the ratio (L2 / L1) in the cross-sectional image of the first cross-section.

4. The substrate further comprises a resin layer located on the other surface side, The aforementioned resin layer includes a resin portion and a filler. The conductive film according to claim 1, wherein the arithmetic mean roughness of the first surface in the cross-sectional image is greater than the arithmetic mean roughness of the surface of the resin layer.

5. The conductive film according to claim 1, wherein the aspect ratio obtained by dividing the height dimension of the conductive wire by the width dimension is greater than 1.

6. The conductive film according to claim 1, wherein the conductor constitutes a pattern in which the conductive wires are arranged in a mesh-like manner.

7. A display device comprising a conductive film according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Transparent conductive film and method for manufacturing transparent conductive film

    JP2021163571A